2019
DOI: 10.9734/ijtdh/2019/v40i130219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Correlates of Seropositive HIV and HBsAg Cases among Women Booking for Antenatal Care at the Rivers State University Teaching Hospital, Nigeria

Abstract: Background: Infection with hepatitis B (HBV) and human immunodeficiency virus (HIV) are global public health problems. These infections during pregnancy increase the risk of maternal morbidity and mortality, and also pose a risk to the fetus due to mother to child transmission. Objective: To determine the prevalence of seropositive HIV and HBsAg cases amongst pregnant women at the Rivers State University Teaching Hospital (RSUTH). Methodology: A retrospective review of hospital and laboratory recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The mean gestational age at booking of the respondents in this study was 23.0 ± 6.6 weeks. This is similar to the finding at Port-Harcourt, Nigeria, where the authors reported a mean of 22.1 ± 6.8 weeks (Awoyesuku et al, 2019). A much lower mean gestational age at booking of 18.9 ± 7.8 weeks was found by Adegbola & Kuku (2015) in Lagos and 19.4 ± 8.14 weeks in Abuja, North-Central Nigeria (Zaman et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The mean gestational age at booking of the respondents in this study was 23.0 ± 6.6 weeks. This is similar to the finding at Port-Harcourt, Nigeria, where the authors reported a mean of 22.1 ± 6.8 weeks (Awoyesuku et al, 2019). A much lower mean gestational age at booking of 18.9 ± 7.8 weeks was found by Adegbola & Kuku (2015) in Lagos and 19.4 ± 8.14 weeks in Abuja, North-Central Nigeria (Zaman et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Onoh et al, (2012) in a south-eastern state reported a similar prevalence of 83.1%. Considering booking by trimester, 11.1% booked during the first trimester while the majority of the respondents (54.2%) initiated their antenatal care during the second trimester which is in line with the findings from the Port-Harcourt study where the majority booked in the second trimester (Awoyesuku et al, 2019). These findings demonstrated the continuing problem of late antenatal booking in Nigeria and many other developing countries, which are not in line with the WHO recommendation (Adegbola & Kuku, 2015; Adekanle & Isawumi, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations